2017
DOI: 10.1002/cam4.1238
|View full text |Cite
|
Sign up to set email alerts
|

High circulating miR‐18a, miR‐20a, and miR‐92a expression correlates with poor prognosis in patients with non‐small cell lung cancer

Abstract: The purpose of this study was to assess the predictive value of angiogenic miRNAs for disease‐free survival (DFS) and overall survival (OS) of patients with non‐small cell lung cancer (NSCLC). In total, 196 patients with NSCLC (tumor lymph nodes metastasis (TNM) stage I–III) were enrolled and peripheral blood samples were collected. Total RNA was extracted from blood samples, and the relative expression levels of candidate miRNAs were evaluated by real time‐polymerase chain reaction (RT‐PCR). The median follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 45 publications
2
50
0
1
Order By: Relevance
“…Third through checking the full-text and data integrity, 46 articles were further excluded. Finally, 13 studies that met all the inclusion criteria were included in the present study, containing 5 studies on the diagnostic accuracy of miR-126 and NSCLC [19][20][21][22][23] and 8 studies on miR-126 and the prognosis of NSCLC [16,[24][25][26][27][28][29][30]. Specific screening flow chart was presented in Figure 1.…”
Section: Literature Research and Characteristic Of Studiesmentioning
confidence: 99%
“…Third through checking the full-text and data integrity, 46 articles were further excluded. Finally, 13 studies that met all the inclusion criteria were included in the present study, containing 5 studies on the diagnostic accuracy of miR-126 and NSCLC [19][20][21][22][23] and 8 studies on miR-126 and the prognosis of NSCLC [16,[24][25][26][27][28][29][30]. Specific screening flow chart was presented in Figure 1.…”
Section: Literature Research and Characteristic Of Studiesmentioning
confidence: 99%
“…Then we did a bioinformatics study based on public miRNA array data and demonstrated that miR-20a-5p as a candidate to regulate WTX. It was reported that miR-20a was highly expressed in hepatocellular carcinoma [43], lung cancer [44], colon cancer [45] and other tumors [46,47] and acts as an oncogene. And miR-20a can be used as a biomarker in the diagnosis and prognosis of GC [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study revealed that miR-18a may be highly expressed in lung cancer and may function as an oncogene in the development of the disease (17). Increased circulating miR-18a may also be a prognostic factor for lung cancer (18). A meta-analysis revealed that miR-18a may be a promising biomarker for the diagnosis of patients with gastric carcinoma (19).…”
Section: Discussionmentioning
confidence: 99%